CHARACTER EDUCATIONAL VALUES ON “AQUAMAN” MOVIE - Esianita, Pola; Widyawati, Wiwin (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
The purposes of doing this research are to find out the types of character education values found in the Aquaman movie, (ii) recognize the character educations values are found in the Aquaman movie that possibly increase student motivation. In this research, the researcher used library research. The data of this research are character educational values in the conversation among the characters of the “Aquaman” movie. The data source in this research is a movie entitled “Aquaman”. The result shows that there are 15 types of character educational value spoken by the characters. They are: honesty, tolerance, dicipline, hardworking, creativity, curiosity, national spirit, patriotism, friendly/communicative, peacemaker, environmental care, responsibility, loaylity, respect, love & afferction. Then, the most dominant Educational values in this movie is responsible and peacemaker value.